MODIFIKASI ALAT BANTU PEMBUATAN DODOL YANG ERGONOMIS UNTUK MENGURANGI KELUHAN PEKERJA DI UMKM DODOL DI TANGERANG - Priantoraharjo, Shafa Alauddino; Widodo, Lamto; Andres (Jurnal Mitra Teknik Industri, 2024)
In the production process, IMK usually produces in traditional ways and has not automated. This means that the production process depends on human labor. Therefore, a review was carried out on one of the IMK that carried out Dodol production. To produce dodol food takes 8 to 10 hours of work. Initial observations were made to find out what problems could be used as research topics, based on initial observations made in the study, a problem topic was found in Dodol MSMEs in Tangerang. The highest complaints are felt on the back, soles of the feet, knees, and elbows. After a work risk analysis using the REBA and WERA methods, it was found that the risk in the dough kneading process was found to be high and changes needed to be made. Therefore, the design was carried out by considering ergonomic aspects, using the SCAMPER method. After the design, a simulation was carried out with the help of blender software to determine changes in REBA and WERA scores. Three design was created and the third design was chosen as the final design, with a height of 170 cm and a widht of 134 cm. It was found that the new design REBA score is 3 which is classified as low risk and the WERA score is 23 which is also classified as low risk.